ANALISA KRITIS TERHADAP PENENTUAN MASA DALUARSA DALAM TINDAK PIDANA PEMALSUAN SURAT - Aris Sardister Gultom; Rasji Rasji (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Indonesia is a state based on law. In the conception of the rule of law, it is determined that every action of a state administrator must be based on applicable law. The legal system that applies in Indonesia is the Continental European legal system (civil law system) with the main characteristic that the law will only have binding power if it is materialized in the form of statutory regulations. Where the main emphasis on this legal principle is legal certainty. Legal certainty extends beyond the limited interpretation to the material of legislation contained within itself, but legal certainty must be interpreted as a legal guarantee for justice and norms of kindness to the people. Therefore, it is important that there is harmony between the material contained in the legislation and the legal ideals stipulated in the Indonesian state. So that the law is authoritative, just and beneficial for the people of Indonesia. In practice, the existing laws and regulations have yet to provide legal certainty, justice or benefits for the justice seekers community (Justiciabelen), for example, the provisions contained in Article 78 paragraph (3) of the Criminal Code regarding expiration are determined;